reologicheskie svoistva krovi v sisteme kopleksnoi otsenki krovoobrashcheniya u vysokokvalifitsirovanykh sportsmenov - Vikulov, A. D. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
To reveal the relative input the hemarheological changes in the trained athlete's organism at rest was the purpose of the study. The elite athletes (n=13) and nonathletes (n=15) had been distributed over control and experimental groups. The methods of echocardiography, visñosimetry and others had been used. The data had been analised by the factorial method. The study had allowed to state the steadiness of the factorial structure of the trained athletes. The parameters of the bloods's rheological properties dominated in three factors from seven, discriminated in the control and experimental groups. Mechanical properties of the blood had demonstrated connections with the vascular component.